2016
DOI: 10.2174/1871527315666151110125704
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Testosterone Supplementation on Cognitive Functioning in Older Men.

Abstract: Reduction in testosterone levels in men during aging is associated with cognitive decline and risk of dementia. Animal studies have shown benefits for testosterone supplementation in improving cognition and reducing Alzheimer’s disease pathology. In a randomized, placebo-controlled, crossover study of men with subjective memory complaint and low testosterone levels, we investigated whether testosterone treatment significantly improved performance on various measures of cognitive functioning. Forty-four men wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 38 publications
4
46
0
1
Order By: Relevance
“…The adverse impact of TD on mood and depressive symptoms has been reported in several studies [355565758596061]. Although the magnitude of improvements differed among the various studies, a link between TD, mood and depressive symptoms exists.…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse impact of TD on mood and depressive symptoms has been reported in several studies [355565758596061]. Although the magnitude of improvements differed among the various studies, a link between TD, mood and depressive symptoms exists.…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…Observational studies of 799 men on T therapy showed 22% reduction in fatigue scores over 6 months [57]. A modest improvement on global cognition with T therapy was also reported (Table 1) [61]. …”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…There is also evidence that cognitive function could be influenced by testosterone levels (Barrett‐Connor, Goodman‐Gruen, & Patay, ; Moffat et al, ). Low testosterone levels in older men appear to be associated with cognitive decline and risk of dementia (Wahjoepramono et al, ). However, there is conflicting evidence showing that cognitive function does not suffer any interference from testosterone intake (Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In women, circulating estradiol levels experience a substantial decline during menopause, whereas post-menopausal women continue to demonstrate a range of circulating testosterone levels that continue to be lower than levels in men [17]. Despite this sex difference in hormone levels, most studies examining links between testosterone and AD-related outcomes have been solely in men [18][19][20][21][22][23], and the link between testosterone and Tau has been minimally examined in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestive of a more causative than consequential role for testosterone on AD-related outcomes, longitudinal studies have shown that low free and/or total testosterone levels precede development of AD dementia [23] and cognitive dysfunction on measures of global cognition [26,29] and episodic memory [29] . Furthermore, exogenous testosterone supplementation led to improved performance over time in a range of cognitive domains including global cognition [19,33], psychomotor speed [33], executive function [33], osterone on AD-related outcomey ni cant contributor tonitive impairmentthey suggest that the f AD pathology and that this cogand spatial and verbal memory [34,35], although not always [36].…”
Section: Introductionmentioning
confidence: 99%